A 3D exact analysis of the boundary layer effect of asymmetric piezoelectric laminates with electromechanical coupling. (15th October 2015) - Wu, Zhangjian; Han, Chao; Niu, Zhongrong
Abstract: A hybrid analysis of the interfacial stresses near the free edges of piezoelectric unsymmetrical laminated plates under uniform extension is presented based on three-dimensional piezoelasticity. A state space equation for cross-ply asymmetric piezoelectric laminates is obtained by considering all the independent elastic and piezoelectric constants of the laminates. The equation satisfies the open-circuit electric, free boundary conditions at two opposite free edges. Using a transfer matrix and a recursive solution approach, a three-dimensional exact solution has been derived and this has been validated by comparing analytical results with those from finite element analyses. Discussion and comments on solutions obtained using the equations proposed are presented. Since all the continuity conditions across the interfaces between material layers are satisfied, the concentrations of interfacial stresses near free edge boundaries are determined precisely. The significant electromechanical influence of the boundary layer effect is found quantitatively.